ANALYSIS SWOT (STRENGTHS, WEAKNESS, OPPORTUNITY, THREATS) AND STRATEGIC MANAGEMENT CASE STUDIES: PT HARMONY LAND GROUP IN THE PROPERTY MARKETING INDUSTRY IN THE COVID 19 ERA - Ramadani, Ramadani; Dwianto, Agung Surya (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The COVID-19 pandemic has had a significant impact on partial business sectors. One of the businesses affected is the property business. That's why a SWOT analysis is needed in the property marketing industry to answer step optimization. This study aims to identify SWOT in the property marketing industry of PT Harmony Land Group in the Pandemic Era. The purpose of this study is to map and analyze Strengths (Strengths), Weaknesses (Weaknesses), Opportunities (Opportunities), Threats (Threats) in the industry management rights to the industry. We also know that the natural phenomenon of covid 19 is possible to create a tremendous impact on variable business sectors. There are businesses that go up, there are new businesses, there are businesses that are decreasing, and some businesses are closing. Through SWOT analysis in the property marketing industry, we are able to see the strength we will maintain, the weaknesses we will strengthen and minimize, the opportunities we must take and the threats we create solutions for. In this case, PT Harmony Land Group as one of the affected property companies was able to survive in the midst of the onslaught of the COVID-19 pandemic and was able to create strategic management into an execution in the field of property marketing so as to make the company sustainable to date and create new opportunities that have yetEmerged. COVID-19 during the COVID-19 pandemic.